Labor and employment sphere in the conditions of the digital economy: development prospects - A. D. Kirillova; A. V. Popov (Вестник университета)
The article provides an analysis of the digital transformation consequences for the development of the field of labor and employment. Particular attention is paid to the issues of job replacement, employment de-standardisation and structural shifts in the labor market as a whole. The information base of the research is made up of Russian and foreign literature, analyzed using general scientific methods. The results of the analysis confirmed the profound nature of the changes taking place which must be considered as an objective process of forming a new paradigm of the labor market with its advantages and disadvantages. This is most characteristically manifested in the widespread use of non-standard employment forms (platform, remote, etc.) which, among other things, carry a lot of risks for the younger generation. In turn, the threats of large-scale technological unemployment are seen as somewhat exaggerated, as evidenced by research, while the problem of polarization of the labor market is much more real. Summing up, authors have concluded that there is a need to improve public policy in the field of labor and employment to overcome challenges of the digital age.